Factors influencing SRI fund performance - Halil Kiymaz (Journal of Capital Markets Studies (JCMS), 2019)
Purpose - The purpose of this paper is to examine socially responsible investment (SRI) fund performance and investigate the factors influencing fund performance. Design/methodology/approach - The study uses return data from the Morningstar database for 152 SRI funds from January 1995 to May 2015. The initial analysis includes the use of various risk-adjusted performance measures, including Sharpe ratio, Treynor ratio, Information ratio, Sortino ratio and M2. The study also uses four factor models, including Jensen single-factor model, Fama-French three-factor model, Carhart four-factor model and Fama-French five-factor model to explain SRI fund returns. Finally, a cross-sectional regression analysis is applied to investigate the determinants of SRI fund returns. Findings - The results show that, on average, the SRI funds provide comparable risk-adjusted returns relative to various benchmark market indices. Market factor is significant in explaining SRI fund returns. Examining each factor model, the results do not support Fama-French's three-factor model as neither size nor value factor is significant. The author finds weak support for Carhart's momentum factor along with the market factor. Finally, the Fama-French five-factor model shows market, size and operating profit factors explain SRI fund returns. The study also finds the fund performance is stronger for funds with the higher turnover ratio, the larger fund size and more managerial experience and lower for funds with higher expense ratio. Also, funds formed with negative screening perform better than positive or mixed screened funds. Originality/value - SRI funds have received considerable attention from investors. This study contributes to the literature by examining SRI fund performance and investigating factors influencing their performance using multiple factor models and cross-sectional regression analysis. The findings are relevant for investors who demand responsible investment opportunities without sacrificing returns for nonfinancial screenings. Findings also suggest that investors should consider fund characteristics when selecting SRI funds.
Keywords: 330; Factor models; SRI funds; Responsible investment